Role of miR-101-3p/RAP1B axis and insulin protection in glucose-induced stress in HK-2 cell model for diabetic kidney disease - Devaraju, Premala; C. Thambiah, Subashini; Ling, King Hwa; Zahari Sham, Siti Yazmin (Springer, 2026)
Proximal tubular cell (PTC) injury is a critical driver of diabetic kidney disease (DKD). This study aimed to characterize the molecular response of HK-2 PTCs to acute glucotoxicity, focusing on the miR-101-3p/RAP1B axis, insulin-mediated protection, and the primary mechanisms of cell death. HK-2 cells were exposed to varying glucose concentrations (5.5–128 mM) with or without insulin (10 mg/L) for 48 h. We assessed cell viability, mitochondrial membrane potential (ΔΨm), and intracellular reactive oxygen species (ROS). Expression of miR-101-3p, RAP1B, insulin receptor substrates (IRS1/2), and apoptotic proteins (BCL-2, Cytochrome c) was quantified by qPCR and Western blotting. High glucose induced dose-dependent cell death, which was potently rescued by insulin, particularly at 25 mM glucose (viability restored from 76% to 98%, p < 0.0001). This protection strongly correlated with significant RAP1B protein upregulation (p < 0.05), while miR-101-3p expression remained stable. Mechanistically, severe hyperglycemia (128 mM) caused a profound collapse in ΔΨm (p < 0.01) and increased Cytochrome c levels, without a corresponding rise in ROS. Furthermore, severe hyperglycemia suppressed IRS1 expression, potentially limiting insulin’s protective capacity. Acute PTC injury from glucotoxicity is primarily driven by mitochondrial dysfunction and intrinsic apoptosis, rather than by classic oxidative stress. The strong association between insulin mediated survival and RAP1B upregulation suggests the RAP1B signalling pathway as a key component of the PTC defence against hyperglycaemic stress. This work provides a refined model of PTC injury and highlights the RAP1B axis as a promising potential therapeutic target in DKD.